Memahami Pendidikan Islam Berdasarkan Tafsir Ayat-Ayat Ilmu Pengetahuan dalam Al-Qur'an - Satria Kharimul Qolbi (EL-TARBAWI, 2020)
Education is very much related to knowledge and science. Therefore, it is important to understand education on the concept of knowledge. In this context, in order to understand the concept of education in Islam, we need to scrutiny the verses on which al-Qur’an talk about knowledge and science. This method of writing thematically collects the verses of the al-Qur'an that discuss a certain topic and arranges them as much as possible according to the period of their revelation. With deductive reasoning, we draw conclusions from various theories and reviews. Science is the effort from a process carried out by methods and produces a systematic and structured new knowledge that will be used as a basic guideline for humans. There are three laws on learning difference sciences: compulsory, sunnah and haram. One of the most important benefit of learning is increasing the dignity of learners. Application in science can be done early in formal education in accordance with the verses of the Al-Quran.